580 Percutaneous coronary intervention or medical therapy as initial management strategy of patients with spontaneous coronary artery dissections: insight from the multicentre, international dissezioni spontanee coronariche (disco) registry. (8th December 2021) - Benenati, Stefano; Giacobbe, Federico; Zingarelli, Antonio; Alessandra, Truffa Giachet; Lombardi, Primiano; Musumeci, Giuseppe; Cinconze, Sebastian; Barbero, Umberto; Iannaccone, Mario; Patti, Giuseppe; Rognoni, Antonio; Menunni, Marco; et al.
Abstract: Aims: Whether patients with spontaneous coronary artery dissection (SCAD) should undergo an initial conservative management or immediate revascularization through percutaneous coronary intervention (PCI) remains debated. To investigate the frequency and predictors of choosing a strategy of immediate PCI for SCAD, and to compare the clinical outcomes of immediate PCI patients with those undergoing an initial strategy of medical management. Methods and results: 369 patients enrolled in the multicentre international DIssezioni Spontanee COronariche (DISCO) registry between January 2009 and December 2020 were included. The primary endpoint was major adverse cardiovascular events (MACE), a composite of cardiac death, non-fatal myocardial infarction (MI) and any PCI. 240 (65%) patients underwent initial medical management, whereas 129 (35%) had immediate PCI. PCI patients presented more frequently with ST segment-elevation myocardial infarction (STEMI) (68.2% vs. 35%, P < 0.001) and had higher frequency of proximal coronary segment SCAD (31.8% vs. 6.7%, P < 0.001), Thrombolysis in Myocardial infarction (TIMI) flow grade 0–1 (54.3% vs. 20.4%, P < 0.001) and multivessel SCAD (18.6% vs. 9.2%, P = 0.015), as well as a more severe diameter stenosis [99% (100–90) vs. 90% (99–75), P < 0.001]. At multivariate logistic regression, STEMI at presentation (vs. NSTE-ACS, OR: 3.30 95% CI: 1.56–7.12, P = 0.002), proximal coronary segment involvement (OR: 5.43, 95% CI: 1.98–16.45, P = 0.002), TIMI flow grade 0–1 and 2 (respectively, vs. grade 3: OR: 3.22 95% CI: 1.08–9.96, P = 0.038; and OR: 3.98; 95% CI: 1.38–11.80, P = 0.009) and diameter stenosis (per 5% increase, OR: 1.13; 95% CI: 1.01–1.28, P = 0.037) were predictors of immediate PCI, whereas the angiographic subtype 2B predicted a conservative approach (OR: 0.25; 95% CI: 0.07–0.83, P = 0.026). The frequency of in-hospital major adverse cardiac events did not differ between medically and PCI-treated patients. At 2-year follow-up, there were no differences with respect to the composite of MACE (11.7% vs. 13.9%, P = 0.47) and the individual components of cardiovascular death (0.4% vs. 0.7%, P = 0.65), non-fatal MI (8.3% vs. 9.3%, P = 0.92), and any PCI (8.7% vs. 12.4%, P = 0.23). Conclusions: The choice between an immediate medical or PCI management of SCAD is mostly driven by clinical presentation and procedural aspects. In the DISCO cohort, the primary treatment approach was not associated with the risk of short-to-midterm adverse events.